Estradiol causes the rapid accumulation of cAMP in human prostate. - Nakhla, A M (1994)
Androgens are widely acknowledged to be central to the pathogenesis of benign prostatic hypertrophy (BPH). However, BPH increases in prevalence as men age, at precisely the stage of life when plasma androgens are decreasing. The decrease in total plasma androgens is amplified by an age-related increase in plasma sex hormone-binding globulin (SHBG) that results in a relatively greater decrease in free androgens than in total androgens. In addition, estrogens have long been suspected to be important in BPH, but a direct effect on the human prostate has never been demonstrated. We present data that are consistent with a role for estradiol, and for a decrease in androgens and an increase in SHBG, in the pathogenesis of BPH. We show that estradiol, but not dihydrotestosterone, acts in concert with SHBG to produce an 8-fold increase in intracellular cAMP in human BPH tissue. This increase is not blocked by an antiestrogen and is not provoked by an estrogen (diethylstilbestrol) that does not bind to SHBG, thus excluding the classic estrogen receptor as being operative in these events. Conversely, dihydrotestosterone, which blocks the binding of estradiol to SHBG, completely negates the effect of estradiol. Finally, we demonstrate that the SHBG-steroid-responsive second-messenger system is primarily localized to the prostatic stromal cells and not to the prostatic epithelial cells. Thus, we have shown a cell-specific, powerful, nontranscriptional effect of estradiol on the human prostate.